PHYSICAL ACTIVITY AND ANXIETY IN STUDENTS (CIPEEX, 2025)
Introduction: Test anxiety is characterized by psychological, physiological, and behavioral reactions that occur in evaluation situations and affect academic performance and the mental health of students. Physical activity has been identified as a potential intervention to mitigate anxiety. Thus, the objective of this study is to analyze the effects of physical activity on test anxiety in students from full-time schools. Methods: A randomized clinical trial was conducted with 237 students from the 8th grade (final years of elementary school) to the 3rd year of high school, divided into group 01 (GPAF, n=122), which underwent a physical activity protocol: diaphragmatic and frenal breathing exercises combined with stretching, and group 02 control (GC, n=115) without the protocol. Data on body composition (bioimpedance), anxiety (CTAR25), physical activity levels (steps), and changes in heart rate variability (HRV), along with series, age, and sex, were collected from the participants. Statistical analysis was performed using a statistical package (SPSS, v 27.0, IBM), with descriptive data presented as mean, standard deviation, and parametric and non-parametric tests. Results: There were autonomic changes in group 1 (GPAF) compared to group 2 (GC), indicating an association between physical activity and test anxiety. The anxiety levels observed (CTAR25) showed that 78.8% of females demonstrated moderate to high anxiety and that 81.9% of students identified as sedentary. The body composition of students showed data within the normal range for age and sex. Conclusions: There are effects of physical activity on test anxiety.
Keywords: test anxiety; autonomic control; physical activity; mental health